Fuel starvation in automotive PEMFC stacks: a self-enhancing overheating mechanism - Jens Nissen; Jan-Peter Boye; Max Schrievers; Jan Nicolas Schwämmlein; Caroline Willich; Markus Hölzle (JPhys Energy)
The irregular operation state of fuel gross starvation can endanger the robustness of low temperature proton exchange membrane fuel cell stacks. Such detrimental effects of fuel starvation are typically investigated on the level of lab-scale single cells. This publication aims to point out which scale-up phenomena must be taken into consideration when transferring results from such small single cells to the integration level of multi-cell stacks with fuel cells of larger format. A test cycle was developed and conducted, which provoked fuel starvation in only one single fuel cell within a 20-cell stack. This test was performed for two variants of this fuel cell stack. One experimental setup operated the fuel starved cell under local equal voltage. Fuel cells are expected to face this condition when operated as single cells or in multi-cell stacks containing highly conductive metallic bipolar plates (BPs). The other setup intentionally enhanced effects of electric interaction between adjacent fuel cells by using carbon composite BPs. The fuel starved cell under local equal voltage showed an unexpected fast and very steep decrease in cell voltage to $ - 10\,{\text{V }}$ . At such severe conditions, the ionomer membrane suffered a destructive electric break-down. However, this detrimental behavior was not observed for the cell that was in electrical interaction with adjacent cells. The temporally and spatially resolved current density distribution and local temperature of the fuel starved cell in both stack types was investigated. These investigations implied that the cell under local equal voltage suffered a self-enhancing overheating mechanism, which ultimately led to its destruction. It was furthermore presented why the cell in the stack with carbon BPs was able to circumvent such overheating and destruction.